2020
DOI: 10.1073/pnas.2001678117
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-assisted radiant cooling for expanding thermal comfort zones globally without air conditioning

Abstract: We present results of a radiant cooling system that made the hot and humid tropical climate of Singapore feel cool and comfortable. Thermal radiation exchange between occupants and surfaces in the built environment can augment thermal comfort. The lack of widespread commercial adoption of radiant-cooling technologies is due to two widely held views: 1) The low temperature required for radiant cooling in humid environments will form condensation; and 2) cold surfaces will still cool adjacent air via convection,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…However, the early hydronic chilled ceiling system developed in the 1930s was unsuccessful due to the high condensation risk. Condensation remains one of the most significant problems of radiant cooling systems and prevented radiant cooling from being widely utilised for several decades [76]. Condensation can also reduce the air quality of a conditioned space and reduce the thermal efficiency of the radiant cooling systems [63].…”
Section: Radiant Coolingmentioning
confidence: 99%
“…However, the early hydronic chilled ceiling system developed in the 1930s was unsuccessful due to the high condensation risk. Condensation remains one of the most significant problems of radiant cooling systems and prevented radiant cooling from being widely utilised for several decades [76]. Condensation can also reduce the air quality of a conditioned space and reduce the thermal efficiency of the radiant cooling systems [63].…”
Section: Radiant Coolingmentioning
confidence: 99%
“…The thermal radiation transparent membrane separates the chilled surface from the ambient air while still allowing for radiative exchange between the occupants and the panels. The supply temperature can be 13°C lower than the dew point temperature (Teitelbaum, Chen, et al, 2020) or lowered to 7°C, 14.4°C and 19.3°C when the relative humidity is 65%, 80% and 90%, respectively (Xing et al, 2020) without condensation. Thus, overcoming the condensation and cooling capacity limitation when running in a naturally ventilated space.…”
Section: Membrane-assisted Radiant Cooling Panelsmentioning
confidence: 99%
“…The Cold Tube pavilion was used as an apparatus to evaluate the effectiveness of the membrane-assisted cooling panels through physiological measurements and thermal comfort studies (Teitelbaum, Chen, et al, 2020). Physiological measurements have shown that the radiant panels can provide a significant amount of cooling through radiant exchanges only, and it is possible to independently control radiant exchange in a naturally ventilated space without much effect on the air temperature.…”
Section: Membrane-assisted Radiant Cooling Panelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an indoor environment, where most people stay in a sedentary state, more than 50% of the heat generated by the human body is released through thermal radiation in the long-wave infrared part of the spectrum ( Arslanoglu and Yigit, 2016 ). A recent experimental study used a membrane-assisted radiant cooling system to show that radiation and convection can be separated for comfort conditioning and, relying on radiation alone, thermal comfort can be maintained based on existing metrics even in unusually high ambient air conditions ( Teitelbaum et al., 2020 ). Radiative heat transfer between human occupants and their environment largely depends on the radiative properties of clothing, the walls, and other surroundings.…”
Section: Introductionmentioning
confidence: 99%